2020
DOI: 10.1158/1940-6207.capr-19-0427
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Use and the Risk of Cancer in Patients with Diabetes: A Nationwide Sample Cohort Study

Abstract: Metformin is known to have an antitumor effect; however, its effects in the prevention of cancer remain controversial. This study aimed to investigate the association of metformin therapy with the development of cancer. A population-based cohort study was conducted among adult patients with diabetes in 2010 using sample cohort data from the National Health Insurance Service. Metformin users were defined as those who had been prescribed repeated oral metformin administration over a period of !90 days. The prima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“… 82 Seven years later, Oh TK and Song IA conducted a nationwide sample cohort study to analyze the relationship of metformin use and cancer in diabetes patients. 83 The authors found a lack of an association between metformin treatment and the risk of cancer among diabetic patients, even in the high daily dosage groups (>1 g/day). 83 However, there might be some confounders or time bias in this study.…”
Section: Effect Of Metformin On Malignant Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“… 82 Seven years later, Oh TK and Song IA conducted a nationwide sample cohort study to analyze the relationship of metformin use and cancer in diabetes patients. 83 The authors found a lack of an association between metformin treatment and the risk of cancer among diabetic patients, even in the high daily dosage groups (>1 g/day). 83 However, there might be some confounders or time bias in this study.…”
Section: Effect Of Metformin On Malignant Tumorsmentioning
confidence: 98%
“… 83 The authors found a lack of an association between metformin treatment and the risk of cancer among diabetic patients, even in the high daily dosage groups (>1 g/day). 83 However, there might be some confounders or time bias in this study. Thus, further prospective, large population-based cohort studies are needed to confirm these findings.…”
Section: Effect Of Metformin On Malignant Tumorsmentioning
confidence: 98%
“…In this line, Oh et al, conducted a study to investigate the association of metformin therapy with the development of cancer [80]. A total of 66,627 adult subjects with type II diabetes were included in the analysis; 29,974 were metformin users and 36,653 were controls [80].…”
Section: Metformin and Cancermentioning
confidence: 99%
“…In this line, Oh et al, conducted a study to investigate the association of metformin therapy with the development of cancer [80]. A total of 66,627 adult subjects with type II diabetes were included in the analysis; 29,974 were metformin users and 36,653 were controls [80]. After multivariable adjustment, the risk for the development of cancer among metformin users was not significantly different from that among controls (HR = 0.96; 95% confidence interval, 0.89-1.03; p = 0.250), suggesting a lack of association between metformin therapy and the risk of cancer among patients with diabetes [80].…”
Section: Metformin and Cancermentioning
confidence: 99%
See 1 more Smart Citation